2009
DOI: 10.1177/0021998309345354
|View full text |Cite
|
Sign up to set email alerts
|

Design and Test of a Multitooth Tool for CFRP Milling

Abstract: This article deals with the new development of a family of router milling tools for the high-performance milling of carbon fiber reinforced plastics. The new milling tools are shaped by multiple left-hand and right-hand helical edges, which form small pyramidal edges along the cutting length. Several substrates and coatings have been tested including AlTiN and the new naCO with nanocrystalline structure. After the analysis of tests and modifications on the tool prototypes, the final result is a series of routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 15 publications
2
62
0
Order By: Relevance
“…Recently, Hintze et al [22] investigated machining CFRPs during slot milling experiments and observed that occurrence of delamination is closely related to tool wear and top layer fiber cutting angle. Lopez de Lacalle et al [23] studied the performance of multi-tooth cutting tools during the trimming process of CFRPs. They found that the performance of multi-tooth cutting tools with TiAlN coating was superior to straight edge PCD tools for finishing operations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hintze et al [22] investigated machining CFRPs during slot milling experiments and observed that occurrence of delamination is closely related to tool wear and top layer fiber cutting angle. Lopez de Lacalle et al [23] studied the performance of multi-tooth cutting tools during the trimming process of CFRPs. They found that the performance of multi-tooth cutting tools with TiAlN coating was superior to straight edge PCD tools for finishing operations.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the friction coefficient obtained in this work not only reflects the average friction behaviors but also illustrates the local relation between friction force and normal forces, like the maximum or minimum friction coefficient in Figure 4a. Compared with the results in this work, Lacalle et al [44] defined the specific coefficient Ks = Ftooth/(ap·fz), where Ftooth is the maximum cutting force, ap is the depth of worn surface, and fz is the tooth passing frequency), which is similar to the friction coefficient and reflects the maximum force during cutting.…”
Section: Effects Of Deep Cryogenic Treatment On Tribological Propertiesmentioning
confidence: 81%
“…Unfortunately, the cost of PCD tools is six times higher than uncoated tools, whereas tool life is only three times longer. 8 End mills usually have a very special design suitable for the milling of CFRPs. 9 Helical end mills with two flutes are suitable for rigid or back-supported parts.…”
Section: Introductionmentioning
confidence: 99%